2017
DOI: 10.1021/acs.jctc.7b00041
|View full text |Cite
|
Sign up to set email alerts
|

Acid Gas Adsorption on Metal–Organic Framework Nanosheets as a Model of an “All-Surface” Material

Abstract: To establish a model of metal-organic framework (MOF) surfaces and build an understanding of surface-specific ligand adsorption phenomena in MOFs, we present a computational study exploring multiple models of a series of MOF-2 nanosheet materials, "M-BDCs", with M = Zn, Cu, and Co and BDC = benzene-1,4-dicarboxylate. We study and assess the appropriateness of a series of models ranging from small clusters (18 atoms) to fully periodic sheet models. We additionally study the interactions of these models with aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 63 publications
2
43
1
Order By: Relevance
“…MOF‐based materials with high surface area, large void spaces and controllable surface properties have attracted much attention in the field of gas adsorption and separation, such as CO 2 capture, H 2 and CH 4 purifications, and CH 4 storage . Previous researches have demonstrated that LD MOFs with high aspect ratio and unique physicochemical properties possess superior sorption behaviors over their bulk counterparts . For instance, Marmottini and co‐workers have reported a 1D phosphinate‐based MOF rods for CO 2 uptake .…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…MOF‐based materials with high surface area, large void spaces and controllable surface properties have attracted much attention in the field of gas adsorption and separation, such as CO 2 capture, H 2 and CH 4 purifications, and CH 4 storage . Previous researches have demonstrated that LD MOFs with high aspect ratio and unique physicochemical properties possess superior sorption behaviors over their bulk counterparts . For instance, Marmottini and co‐workers have reported a 1D phosphinate‐based MOF rods for CO 2 uptake .…”
Section: Applicationsmentioning
confidence: 99%
“…[48][49][50] These types of MOFs, such as 1D single-walled MOF nanotubes, 1D hexagonal MOF nanorods, ultrathin 2D MOF nanosheets, [51][52][53] have similar morphological features to those of the other 1D or 2D nanomaterials, which endows them with distinctive dimensional-dependent properties including high aspect ratio and abundant accessible active sites. [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] Although the advantages and challenges of 1D metal-organic nanotubes [76] and 2D MOF nanosheets [48,50,56] have been well summarized by several previous review articles, the research field of LD MOFs is currently at a stage of rapid development, as indicated by annually increased amount of publications (Figure 2). To achieve effective and controllable preparation of LD MOFs, a large number of synthetic methods have been developed, such as template method, ultrasonic exfoliation, surfactant-assisted growth, three-layer method, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33] Taking a different approach, Howe et al looked at the interactions of several gases with the external surfaces of MOFs. [34] Their calculations utilized a number of density functionals and wavefunction and gas molecules. [35] Their methodology uses a decomposition of second-order Møller-Plesset perturbation theory interactions as the basis for the terms of a new force field.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the extensive experimental studies on the adsorption performance of NCCs on HKUST-1, only a few theoretical researches have focused on NCCs’ adsorption behavior in MOFs. A lot of theoretical work has studied the adsorption in various MOFs of small molecules such as CO 2 [ 20 , 21 , 22 ], SO 2 [ 23 , 24 ], dibenzothiophene [ 25 ], CH 4 [ 21 , 26 , 27 ], N 2 [ 21 ], N 2 O [ 28 ], H 2 [ 21 ], and noble gas [ 29 ]. To our best knowledge, a systematic study on the adsorption of three NCCs (NO, NO 2 , and NH 3 ) on 19 metal-substituted variants of HKUST-1 is still missing.…”
Section: Introductionmentioning
confidence: 99%